Effect of Rotation on the Performance of Paddle Wheel Type Pond Waterwheel - Ridwan, Ridwan; Irawan, Rudi (Magister Teknik Mesin Universitas Pancasila, 2025)
Aerator is a very important equipment in fish farming. The availability of sufficient oxygen in the water greatly affects the growth of fish or shrimp in pond cultivation. Besides that, the use of energy in generating or producing dissolved oxygen in ponds cultivation must be as efficient as possible decreasing that cost perations. The purpose of this research was to obtain the best performance of the Paddle wheel type aerator to increasing the dissolved oxygen in pond water with the lowest energy consumption used in producing or increasing the dissolved oxygen in ponds cultivation. The research method was experimentally for the aerator paddle wheel type with eight blades, and 16 holes on each the blade. There were four variations of rotation on the blades or rotors, namely: Rotation per minutes (RPM): 80, 100, 120, and 140. The results of the research showed that at a rotation speed of 120 RPM it provided the most optimal performance, the most efficient use of energy to increase the dissolved oxygen content compared the others RPM.